A high-capacity EFB start-stop battery positive electrode lead paste and preparation method thereof
By combining the capacity-enhancing stabilizer in the positive lead paste of the EFB start-stop battery, the intermediate generated by the reaction of β-mercaptoethylamine and triallyl isocyanurate is combined with graphene nanosheets to form bismuth oxides Doped graphene clusters solve the problem that the positive electrode coating is prone to fall off and significantly improves the battery capacity and cycle stability.
Patent Information
- Application Number
- CN202411687981.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In the automotive start-stop system, the positive electrode coating of the EFB start-stop battery is easily fall off, affecting the battery's service life and cycle stability.
By combining a capacity-enhancing stabilizer in the positive lead paste of the EFB start-stop battery, the capacity-enhancing stabilizer is an intermediate produced by the reaction of β-mercaptoethylamine and triallyl isocyanurate, through silane pairs The coupling agent KH560 is grafted to form a multi-branched ethoxysilane structure and is combined with graphene nanosheets to form bismuth oxide-doped graphene clusters.
It significantly improves the battery capacity and start-stop cycle stability, reduces the fall of the positive electrode coating, extends the battery life, and improves electrochemical performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of storage batteries, and in particular relates to a high-capacity EFB start-stop battery positive electrode lead paste and a preparation method thereof. Background Art
[0002] The car start-stop system refers to the system that automatically shuts down the engine when the vehicle stops temporarily during driving. When it needs to continue moving forward, the system automatically restarts the engine. It is a new energy-saving system that is currently more widely used, and the start-stop battery is more widely used lead-acid start-stop battery; currently AGM and EFB batteries can meet the above needs. Among them, EFB batteries have a larger market share due to their relatively low cost and long life.
[0003] In this start-stop system, when the engine is started frequently, the battery is required to support frequent large current discharge and simultaneous brake energy recovery. During the frequent start-stop process, the positive electrode coating is easy to fall off, which has a great impact on the battery's service life. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-capacity EFB start-stop battery positive electrode lead paste and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-capacity EFB start-stop battery positive electrode lead paste, comprising, by weight:
[0007] 100 parts of lead powder, 2.5-3.2 parts of red lead, 4.6-5.5 parts of a volume-increasing stabilizer, 0.2-0.3 parts of nano-carbon fiber, 0.08-0.1 parts of beta-naphthol and 12-15 parts of sulfuric acid.
[0008] A method for preparing a positive electrode lead paste for a high-capacity EFB start-stop battery comprises the following steps:
[0009] Step S1: dry-mixing lead powder, red lead, a volume-increasing stabilizer, nano-carbon fibers and β-naphthol in a high-speed mixer to obtain a batch;
[0010] Step S2: pre-mix the batch with deionized water accounting for 11-12.5 wt% of the batch mass, and then slowly add sulfuric acid to mix well to obtain a positive electrode lead paste.
[0011] Furthermore, the fineness of the lead powder is not less than 150 mesh.
[0012] The compatibilizing stabilizer is prepared by the following method:
[0013] Step A1: β-mercaptoethylamine and tetrahydrofuran are mixed, and then triallyl isocyanurate is added and mixed, nitrogen is introduced for protection, the temperature is raised to 45-55°C, and 150-200W / m 2 UV irradiation, slowly add azobisisobutyronitrile and stir to react for 1.6-2.2h. After the reaction is completed, remove tetrahydrofuran by rotary evaporation. Wash the substrate with ether and dry it to obtain an intermediate.
[0014] Furthermore, the dosage ratio of triallyl isocyanurate, β-mercaptoethylamine, azobisisobutyronitrile and tetrahydrofuran is 0.1 mol: 0.3 mol: 25-30 mg: 120-150 mL. Under the promotion of azobisisobutyronitrile and the initiation of ultraviolet radiation, the active thiol group of β-mercaptoethylamine is added to the double bond of triallyl isocyanurate to introduce active amino modification.
[0015] Step A2: The intermediate, triethylamine and anhydrous acetone are mixed, the temperature is controlled at 0-10°C in an ice-water bath, and then the silane coupling agent KH560 is slowly added and mixed, and then the temperature is raised to reflux for 1-1.3 hours. After the reaction is completed, the acetone is removed by vacuum drying to obtain a template compound;
[0016] Furthermore, the usage ratio of the intermediate, silane coupling agent KH560, triethylamine and anhydrous acetone is 0.1 mol: 0.3 mol: 12-18 mL: 80-100 mL, the silane coupling agent KH560 and the grafted active amino group in the intermediate are ring-opened, and multi-branched ethoxysilane is introduced for structural modification.
[0017] Step A3: Mix the template compound, ethanol and deionized water, adjust the pH value to 3-4 with formic acid, stir and hydrolyze at room temperature for 1-1.5 hours, then add graphene nanosheets and bismuth nitrate for ultrasonic dispersion and adjust the pH value to 8.5-9.5 with ammonia water, let stand for 24 hours, take the bottom precipitate, dry it and calcine it at 450±5℃ for 3 hours to obtain a volume-increasing stabilizer;
[0018] Furthermore, the usage ratio of graphene nanosheets, template compound, bismuth nitrate, ethanol and deionized water is 50g:3.6-4.2g:0.25-0.3g:150-200mL:80-120mL. The ethoxysilane in the template compound is hydrolyzed in an acidic alcohol-water environment, and the polysulfur-nitrogen structure in its molecular structure forms a chelate to capture bismuth ions. During the alkalinization process of ammonia water, the multi-branched hydrolyzed silanol structure is coupled with the graphene nanosheets, and the hydrolysis of bismuth ions is promoted to form a clustered complex, which is then calcined and formed.
[0019] Furthermore, the diameter of the graphene nanosheet is no greater than 20 μm.
[0020] Beneficial effects of the present invention:
[0021] The present invention significantly improves the capacity and start-stop cycle stability of the battery by compounding a capacity-increasing stabilizer in the positive lead paste of the EFB start-stop battery; the capacity-increasing stabilizer is prepared by adding the active thiol of β-mercaptoethylamine to the double bond of triallyl isocyanurate, introducing active amino groups for modification, and preparing an intermediate; then, a silane coupling agent KH560 is used to open the ring with the active amino groups grafted in the intermediate, and a multi-branched ethoxysilane structure is introduced for modification to prepare a template compound; and through a liquid phase deposition method, the multi-branched ethoxysilane structure of the template compound is combined with graphene nanosheets by utilizing the coupling effect, so as to form fine graphene clusters under an ultrasonic environment. Clusters, in whose structure the polynary sulfur-nitrogen structure forms a chelate to capture bismuth ions, and after calcination, bismuth oxide-doped graphene clusters are formed; when compounded in the positive lead paste, it promotes the formation of active tetrabasic lead sulfate on the surface of the capacity-increasing stabilizer, which promotes the improvement of the electrochemical performance of the battery, and the graphene clusters to which it is attached provide a large number of ion channels, which are beneficial to the deintercalation of ions during the charge and discharge process, thereby improving the capacity of the battery. Moreover, its cluster structure has good toughness, which buffers the positive electrode solidification layer during the start-stop high-frequency charge and discharge process, reduces the shedding of the positive electrode coating, and enables the battery to maintain excellent cycle stability. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1, preparing a high-capacity EFB start-stop battery positive electrode lead paste, specifically as follows:
[0024] (1) Preparation of volume-increasing stabilizer
[0025] Step A1: β-mercaptoethylamine and tetrahydrofuran were mixed and stirred, and then triallyl isocyanurate was added and mixed, and nitrogen was introduced for protection, and the temperature was raised to 55°C, and a UVA light source with a power of 150 W / m 2 Under ultraviolet irradiation, azobisisobutyronitrile was slowly added within 30 minutes. After complete addition, the reaction was continued with stirring. The total addition reaction time of azobisisobutyronitrile was controlled to be 1.6 hours. The dosage ratio of triallyl isocyanurate, β-mercaptoethylamine, azobisisobutyronitrile and tetrahydrofuran was 0.1 mol: 0.3 mol: 30 mg: 150 mL. After the reaction was completed, tetrahydrofuran was removed by rotary evaporation, and the substrate was washed with ether and dried to obtain an intermediate.
[0026] Step A2: Take the intermediate, triethylamine and anhydrous acetone and mix them. The temperature is controlled at 10°C in an ice-water bath. The silane coupling agent KH560 is slowly added and mixed within 10 minutes. After the addition is complete, the temperature is raised and controlled to be 60±2°C and refluxed for 1 hour. The amount ratio of the intermediate, the silane coupling agent KH560, the triethylamine and the anhydrous acetone is 0.1 mol: 0.3 mol: 12 mL: 100 mL. After the reaction is completed, the acetone is removed by vacuum drying to obtain a template compound;
[0027] Step A3: Mix the template compound, ethanol and deionized water, adjust the pH value to 3 with formic acid, stir and hydrolyze at room temperature for 1 hour, then add graphene nanosheets and bismuth nitrate, ultrasonically disperse at 28kHz for 20 minutes, adjust the pH value to 8.5 with ammonia water, and let stand for 24 hours, wherein the amount ratio of graphene nanosheets, template compound, bismuth nitrate, ethanol and deionized water is 50g:3.6g:0.25g:150mL:80mL, and the graphene nanosheets are all selected from the XF021 raw materials of Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a sheet diameter of 5-10μm and a thickness of 3-10nm. Then, the bottom precipitate is taken and dried, and then calcined at 450±5℃ for 3h to obtain a volume-increasing stabilizer.
[0028] (2) Preparation of lead paste
[0029] Ingredients: according to weight, 100 parts of lead powder, electronic grade lead powder of Qingdao Dechen Chemical Co., Ltd., with a 180-mesh sieve residue of no more than 0.2%; 3.2 parts of red lead, electronic grade red lead of Qingdao Dechen Chemical Co., Ltd., with a 325-mesh sieve residue of no more than 0.75%; 4.6 parts of volume-increasing stabilizer, homemade in this embodiment; 0.3 parts of nano-carbon fiber, nano-carbon fiber of Beijing Dekedaojin Technology Co., Ltd., with a fiber length of 10-20 μm; 0.08 parts of β-naphthol, industrial grade raw material, 15 parts of sulfuric acid, self-prepared aqueous solution, density of 1.3 g / cm 3 .
[0030] Step S1: Add lead powder, red lead, a volume-increasing stabilizer, nano-carbon fibers and β-naphthol into a high-speed mixer, and dry-mix at 1200 rpm for 20 minutes to obtain a batch material.
[0031] Step S2: 11 wt% of the mass of the batch of deionized water and the batch are added into a stirrer, stirred at 60 rpm for 10 min, then the stirring rate is increased to 180 rpm, sulfuric acid is slowly added within 10 min to mix well, and a positive electrode lead paste is obtained.
[0032] Example 2, preparing a high-capacity EFB start-stop battery positive electrode lead paste, specifically as follows:
[0033] (1) Preparation of volume-increasing stabilizer
[0034] Step A1: β-mercaptoethylamine and tetrahydrofuran were mixed and stirred, and then triallyl isocyanurate was added and mixed, and nitrogen was introduced for protection, and the temperature was raised to 45°C, and a UVA light source of 200W / m 2 Under ultraviolet irradiation, azobisisobutyronitrile was slowly added within 50 minutes. After complete addition, the reaction was continued with stirring. The total addition reaction time of azobisisobutyronitrile was controlled to be 2.2 hours. The dosage ratio of triallyl isocyanurate, β-mercaptoethylamine, azobisisobutyronitrile and tetrahydrofuran was 0.1 mol: 0.3 mol: 25 mg: 120 mL. After the reaction was completed, tetrahydrofuran was removed by rotary evaporation. The substrate was washed with ether and dried to obtain an intermediate.
[0035] Step A2: Take the intermediate, triethylamine and anhydrous acetone and mix them. Control the temperature at 0°C in an ice-water bath. Slowly add the silane coupling agent KH560 within 20 minutes and mix well. After the addition is complete, heat up and control the temperature at 60±2°C to reflux for 1.3 hours. The amount ratio of the intermediate, silane coupling agent KH560, triethylamine and anhydrous acetone is 0.1 mol: 0.3 mol: 18 mL: 80 mL. After the reaction is completed, vacuum drying is performed to remove acetone to obtain a template compound;
[0036] Step A3: Mix the template compound, ethanol and deionized water, adjust the pH value to 4 with formic acid, stir and hydrolyze at room temperature for 1.5 hours, then add graphene nanosheets and bismuth nitrate, ultrasonically disperse at 28kHz for 20 minutes, adjust the pH value to 9.5 with ammonia water, and let stand for 24 hours, wherein the amount ratio of graphene nanosheets, template compound, bismuth nitrate, ethanol and deionized water is 50g:4.2g:0.3g:200mL:120mL, and the graphene nanosheets are all selected from the XF021 raw materials of Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a sheet diameter of 5-10μm and a thickness of 3-10nm. Then, the bottom precipitate is taken and dried, and then calcined at 450±5℃ for 3h to obtain a volume-increasing stabilizer.
[0037] (2) Preparation of lead paste
[0038] Ingredients: according to weight, 100 parts of lead powder, electronic grade lead powder of Qingdao Dechen Chemical Co., Ltd., with a 180-mesh sieve residue of no more than 0.2%; 2.9 parts of red lead, electronic grade red lead of Qingdao Dechen Chemical Co., Ltd., with a 325-mesh sieve residue of no more than 0.75%; 5.2 parts of volume-increasing stabilizer, homemade in this embodiment; 0.2 parts of nano-carbon fiber, nano-carbon fiber of Beijing Dekedaojin Technology Co., Ltd., with a fiber length of 10-20 μm; 0.1 parts of β-naphthol, industrial grade raw material, 12 parts of sulfuric acid, self-prepared aqueous solution, density of 1.3 g / cm 3 .
[0039] Step S1: Add lead powder, red lead, a volume-increasing stabilizer, nano-carbon fibers and β-naphthol into a high-speed mixer, and dry-mix at 1200 rpm for 20 minutes to obtain a batch material.
[0040] Step S2: Deionized water (12.5 wt% of the mass of the batch) and the batch are added into a stirrer, stirred at 60 rpm for 10 min, then the stirring rate is increased to 180 rpm, sulfuric acid is slowly added within 10 min to mix well, and a positive electrode lead paste is obtained.
[0041] Example 3, preparing a high-capacity EFB start-stop battery positive electrode lead paste, as follows:
[0042] (1) Preparation of volume-increasing stabilizer
[0043] Step A1: β-mercaptoethylamine and tetrahydrofuran were mixed and stirred, and then triallyl isocyanurate was added and mixed, and nitrogen was introduced for protection, and the temperature was raised to 50°C, and a UVA light source with a power of 180 W / m 2 Under ultraviolet irradiation, azobisisobutyronitrile was slowly added within 40 minutes. After complete addition, the reaction was continued with stirring. The total addition reaction time of azobisisobutyronitrile was controlled to be 2 hours. The dosage ratio of triallyl isocyanurate, β-mercaptoethylamine, azobisisobutyronitrile and tetrahydrofuran was 0.1 mol: 0.3 mol: 28 mg: 140 mL. After the reaction was completed, tetrahydrofuran was removed by rotary evaporation. The substrate was washed with ether and dried to obtain an intermediate.
[0044] Step A2: Take the intermediate, triethylamine and anhydrous acetone and mix them. The temperature is controlled at 0°C in an ice-water bath. The silane coupling agent KH560 is slowly added within 20 minutes and mixed. After the addition is complete, the temperature is raised and controlled to be 60±2°C and refluxed for 1.2 hours. The amount ratio of the intermediate, the silane coupling agent KH560, the triethylamine and the anhydrous acetone is 0.1 mol: 0.3 mol: 15 mL: 90 mL. After the reaction is completed, the acetone is removed by vacuum drying to obtain a template compound;
[0045] Step A3: Mix the template compound, ethanol and deionized water, adjust the pH value to 4 with formic acid, stir and hydrolyze at room temperature for 1.3 hours, then add graphene nanosheets and bismuth nitrate, ultrasonically disperse at 28kHz for 20 minutes, adjust the pH value to 9 with ammonia water, and let stand for 24 hours, wherein the amount ratio of graphene nanosheets, template compound, bismuth nitrate, ethanol and deionized water is 50g:4g:0.28g:180mL:100mL, and the graphene nanosheets are all selected from the XF021 raw materials of Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a sheet diameter of 5-10μm and a thickness of 3-10nm. Then, the bottom precipitate is taken and dried, and then calcined at 450±5℃ for 3h to obtain a volume-increasing stabilizer.
[0046] (2) Preparation of lead paste
[0047] Ingredients: according to weight, 100 parts of lead powder, electronic grade lead powder of Qingdao Dechen Chemical Co., Ltd., with a 180-mesh sieve residue of no more than 0.2%; 2.5 parts of red lead, electronic grade red lead of Qingdao Dechen Chemical Co., Ltd., with a 325-mesh sieve residue of no more than 0.75%; 5.5 parts of volume-increasing stabilizer, homemade in this embodiment; 0.2 parts of nano-carbon fiber, nano-carbon fiber of Beijing Dekedaojin Technology Co., Ltd., with a fiber length of 10-20 μm; 0.1 parts of β-naphthol, industrial grade raw material, 14 parts of sulfuric acid, self-prepared aqueous solution, density of 1.3 g / cm 3 .
[0048] Step S1: Add lead powder, red lead, a volume-increasing stabilizer, nano-carbon fibers and β-naphthol into a high-speed mixer, and dry-mix at 1200 rpm for 20 minutes to obtain a batch material.
[0049] Step S2: 11.8 wt% of the mass of the batch was taken from deionized water and the batch, added into a stirrer, stirred at 60 rpm for 10 min, then the stirring rate was increased to 180 rpm, sulfuric acid was slowly added and mixed within 10 min to obtain a positive electrode lead paste.
[0050] Comparative Example: A high-capacity EFB start-stop battery positive electrode lead paste is prepared as follows:
[0051] Ingredients: 100 parts of lead powder, electronic grade lead powder from Qingdao Dechen Chemical Co., Ltd., with a 180-mesh sieve residue of no more than 0.2%; 3 parts of red lead, electronic grade red lead from Qingdao Dechen Chemical Co., Ltd., with a 325-mesh sieve residue of no more than 0.75%; 5 parts of graphene nanosheets, XF021 type raw material; 0.25 parts of bismuth oxide, N100 type nano bismuth oxide from Ningbo Jinlei Nanomaterial Technology Co., Ltd., with a particle size of about 100nm; 0.2 parts of nanocarbon fiber, nanocarbon fiber from Beijing Dekedaojin Technology Co., Ltd., with a fiber length of 10-20μm; 0.1 parts of β-naphthol, industrial grade raw material, 15 parts of sulfuric acid, self-prepared aqueous solution, density of 1.3g / cm 3 .
[0052] Step S1: Add lead powder, red lead, graphene nanosheets, nanocarbon fibers and β-naphthol into a high-speed mixer, and dry-mix at 1200 rpm for 20 minutes to obtain a batch material.
[0053] Step S2: 12 wt% of the mass of the batch is taken from deionized water and the batch, added into a stirrer, stirred at 60 rpm for 10 min, then the stirring rate is increased to 180 rpm, sulfuric acid is slowly added within 10 min to mix well, and a positive electrode lead paste is obtained.
[0054] In order to verify the application performance of the above positive lead paste, it is used in the positive plate to test the relevant performance, as follows:
[0055] Paste coating: Apply the positive lead paste on the grid surface, and then use a press to compact it at 1.2MPa, hold the pressure for 60s, and then immerse it in 1g / cm 3 Dilute sulfuric acid, immerse for 5 seconds, drain and get the paste board;
[0056] Curing: Place the paste-coated board in an autoclave and steam-cure it with saturated steam for 5 hours. Dry the material naturally for 24 hours to obtain a cured board.
[0057] Chemical formation: Total surface area of cured board × 10mV / cm 2 , as the theoretical current, the curing plate and the negative plate are placed in the electrolytic cell with two positive and one negative plates, and 1g / cm 3 The dilute sulfuric acid was subjected to electrochemical reaction at 0.5 times the theoretical current for 2 h, 1.2 times the theoretical current for 10 h, and 0.2 times the theoretical current for 5 h, and the material was dried after discharge to obtain a positive electrode plate;
[0058] Assembly: The positive and negative plates are assembled and welded according to 7 negative and 6 positive, with a thickness of 1.28g / cm 2 Sulfuric acid is used as the electrolyte to assemble the EFB battery.
[0059] After the battery assembled above is fully charged, the battery is tested for 20 hour rate capacity (C 20 ) test; Start-stop test: After the battery is fully charged, discharge at 35±2A for 60s, then charge at 12±1A for 10s, charge and discharge for 1000 cycles and let stand for 24h. After 10000 cycles of charge and discharge, test the battery's 20-hour rate capacity again to calculate the capacity retention rate. The specific test results are shown in Table 1:
[0060] Table 1
[0061]
[0062] It can be seen from the test results in Table 1 that the battery made of the positive electrode lead paste of the embodiment has a 20-hour rate capacity of 53.7-58.4Ah, which is higher than the 49.2Ah of the comparative example. After 10,000 charge and discharge simulated start-stop cycles, the capacity retention rate of the embodiment is 94.92-97.85%, which is 88.17% of the comparative example, and has excellent cycle stability.
[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high-capacity EFB start-stop battery positive electrode lead paste, characterized in that: The composition comprises, by weight: 100 parts of lead powder, 2.5-3.2 parts of red lead, 4.6-5.5 parts of a volume-increasing stabilizer, 0.2-0.3 parts of carbon nanofibers, 0.08-0.1 parts of β-naphthol and 12-15 parts of sulfuric acid; The compatibilizing stabilizer is prepared by the following method: Step A1: β-mercaptoethylamine and tetrahydrofuran are mixed, and then triallyl isocyanurate is added and mixed, nitrogen is introduced for protection, the temperature is raised to 45-55°C, and 150-200W / m 2 UV irradiation, slowly add azobisisobutyronitrile and stir to react for 1.6-2.2h, after the reaction, remove tetrahydrofuran by rotary evaporation, wash the substrate with ether and dry it to obtain an intermediate, wherein the amount ratio of triallyl isocyanurate, β-mercaptoethylamine, azobisisobutyronitrile and tetrahydrofuran is 0.1mol:0.3mol:25-30mg:120-150mL; Step A2: The intermediate, triethylamine and anhydrous acetone are mixed, the temperature is controlled at 0-10°C in an ice-water bath, and then the silane coupling agent KH560 is slowly added and mixed, and then the temperature is raised to reflux for 1-1.3 hours. After the reaction is completed, the acetone is removed by vacuum drying to obtain a template compound, wherein the amount ratio of the intermediate, the silane coupling agent KH560, the triethylamine and the anhydrous acetone is 0.1 mol: 0.3 mol: 12-18 mL: 80-100 mL; Step A3: Mix the template compound, ethanol and deionized water, adjust the pH value to 3-4 with formic acid, stir and hydrolyze at room temperature for 1-1.5 hours, then add graphene nanosheets and bismuth nitrate for ultrasonic dispersion and adjust the pH value to 8.5-9.5 with ammonia water, let it stand for 24 hours, take the bottom precipitate, dry it, and then calcine it at 450±5℃ for 3 hours to obtain a volume-increasing stabilizer, wherein the amount ratio of graphene nanosheets, template compound, bismuth nitrate, ethanol and deionized water is 50g:3.6-4.2g:0.25-0.3g:150-200mL:80-120mL.
2. The high-capacity EFB start-stop battery positive lead paste according to claim 1, characterized in that: The diameter of the graphene nanosheet is no greater than 20 μm.
3. The high-capacity EFB start-stop battery positive lead paste according to claim 1, characterized in that: The fineness of lead powder shall not be less than 150 mesh.
4. A method for preparing a high-capacity EFB start-stop battery positive electrode lead paste according to any one of claims 1 to 3, characterized in that: The steps include: Step S1: dry-mixing lead powder, red lead, a volume-increasing stabilizer, nano-carbon fibers and β-naphthol in a high-speed mixer to obtain a batch; Step S2: pre-mix deionized water and the batch material, then slowly add sulfuric acid and mix well to obtain a positive electrode lead paste.
5. The method for preparing a high-capacity EFB start-stop battery positive electrode lead paste according to claim 4, characterized in that: The deionized water accounts for 11-12.5wt% of the batch mass.
Citation Information
Patent Citations
Graphene coated lead powder composite material and application thereof
CN103579616A
A negative plate lead paste used for starting and stopping lead-carbon super batteries with high performance and a preparation method thereof
CN109103426A